O direito à vida no pensamento de Norberto Bobbio - Pinheiro, Reginaldo César (2019)
The present research is theme of the analysis of Norberto Bobbio's trilogy (notably human rights, democracy and peace), under the focus of the right to life. Bobbio set the Non-Kill! in the sense of protection of life, in its broadest meaning, as being a categorical imperative of kantian model. Therefore, the problem that arises is: how can it be ensured or even promote the right to life, in the spheres of human rights, democracy and peace, in relation to the categorical imperative Non-Kill!? Starting from this premise, it was established as a general objective to analyze the right to life and to live, in the thought of Norberto Bobbio, from the categorical imperative Non-Kill!, where a critical study is intended to carry out Bobbio's ethics and the solution given by him to the protection of life, because human life is a primordial value as a condition for all values. In another respect the study will have as specific objectives to analyze human rights from the perspective of the right to life and the categorical imperative Non-Kill!; contextualize bobbiana procedural democracy as an instrument for promoting the right to life, from the perspective of collective interest; and to analyze the theory of peace as a condition of the right to life and legal pacifism, because when there is no peace the right to life will always be at risk. This research is justified by the fact that Norberto Bobbio was consecrated in the field of general theory of law and philosophy of law, by his theories of the legal norm and the legal system. However, in the field of ethics and philosophy, Bobbio's works are still little widespread in Brazil, so that the study is justified for the purposes of academic-scientific contribution. In addition, Bobbio also proposes the legal pacifism that ultimately legally solves the problem of war. The research will be developed with the use of the deductive method, through the realization of qualitative bibliographic analysis, having as main works L'età dei diritti, Il futuro della democrazia, Il terzo assente and Il problema della guerra e le vie della pace. From a hypothetical point of view, the problem will be solved, with the end of moral relativism and the use of the categorical imperative Non-Kill! as a last value; that respect for procedural democracy contributes to the well-being of the collective; that legal pacifism favors the climate of peace between states and facilitates the promotion of the right to life and to live, since at war all rights are at risk. It is expected, in the guise of results, that it is possible to demonstrate the importance of the categorical imperative Non-Kill! moral conduct to be followed by all.